2007
DOI: 10.1097/01.pec.0000248699.42175.62
|View full text |Cite
|
Sign up to set email alerts
|

Immunization Histories Given by Adult Caregivers Accompanying Children 3-36 Months to the Emergency Department

Abstract: Caregiver report was determined to be inaccurate for Hib and PCV7. Despite 91.5% of caregivers stating that shots were up-to-date, only 66.0% were correct that their child was up-to-date with these 2 vaccines. The ED physician should use caution in making clinical decisions based on the history given by a caregiver regarding their child's immunization status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…This result is similar to those of previous studies in which caregivers brought immunization cards to the ED only 21% to 23% of the time. 25,26,38 Overall, only 6 caregivers in the current study had immunization cards that documented the completion of the primary conjugate vaccine series. Other EDs may have caregivers who are more likely to present with an up-to-date immunization card, thus reducing the impact of an immunization registry.…”
Section: Limitationsmentioning
confidence: 98%
See 2 more Smart Citations
“…This result is similar to those of previous studies in which caregivers brought immunization cards to the ED only 21% to 23% of the time. 25,26,38 Overall, only 6 caregivers in the current study had immunization cards that documented the completion of the primary conjugate vaccine series. Other EDs may have caregivers who are more likely to present with an up-to-date immunization card, thus reducing the impact of an immunization registry.…”
Section: Limitationsmentioning
confidence: 98%
“…Multiple factors may contribute to the inaccuracy of parental reporting of their children's immunization status, including the complexity of the immunization schedule, recent national vaccine shortages causing modifications in vaccine recommendations, and the promotion by some lay groups of alternative vaccine schedules. 25,26,28,29 Emergency medicine (EM) practitioners are frequently unable to confirm a child's immunization status, making it difficult to accurately identify which children presenting with FWS should be considered low risk and eligible for observation rather than blood screening and empiric antibiotic treatment. 25,26,30 In an effort to provide all practitioners with access to up-to-date immunization records, the Centers for Disease Control and Prevention (CDC) has supported initiatives to develop local and state immunization registries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the ED charts, their immunizations were noted to be ''up-to-date,'' although previous studies have demonstrated that parent recollection of immunization status is by no means perfect. 17 The pneumococcal serotypes of those patients are unknown and conceivably may not have been covered by vaccination. The patient with two separate episodes of pneumococcal bacteremia was in the pre-Prevnar time period, and it is plausible that this patient may have benefited from vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization status screening is rarely done routinely outside of primary care facilities, or when it is done (mostly by asking parents), it is often inaccurate. [9][10][11] A key barrier to ascertaining the immunization status of children outside the medical home or primary care setting is lack of access to immunization records. Additionally, highrisk, frequently hospitalized patients are underimmunized because of perceived contraindications or lack of access to convenient primary care despite parental willingness to vaccinate.…”
mentioning
confidence: 99%